Mapping of Internal Audit Quality on the Public Sector in Indonesia: A Systematic Review - Sihombing, Ranto Partomuan (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
This study aims to explore internal audit quality in Indonesia, especially in the public sector. The researcher used a systematic literature review method to synthesize the research results conducted over the past seven years between 2016 and 2022. This study found that most internal audit quality is only output-oriented, primarily influenced by compliance driver variables. The most researched variables are independence and competence. It also adopts attribution theory. However, the kaizen philosophy perspective assesses quality based on the demand-based driver. Finally, this study proposes a conceptual model for developing internal audit quality and future research that should be conducted based on outcomes using a qualitative approach.